Mengungkap Kehidupan Ende Pasar Sotor dalam Lingkungan Keluarga - Kawu, Yuliana; Wiasti, Ni Made; Aliffiati, . (Sunari Penjor : Journal of Anthropology; Vol 7 No 2 (2023): Volume 7. No. 2. September 2023, 2023)
Ende are one of the merchant communities in Sotor Market, Ketang Village, Manggarai Regency, East Nusa Tenggara Province. In everyday life Ende has a dual role, namely a domestic role and a public role. The involvement of women in the public sphere aims to help husbands increase economic family. So on this basis the research was conducted to find out how the role of women traders in the domestic sphere and in the public sphere. The method used in this study is a qualitative method with an ethnographic research model through observation, interviews, and literature studies. The theory used is Role theory (Pujiwati Sajogyo) and Socialist Feminism theory (Friederich Engels). Based on the results of the research analysis, Ende's role in the domestic sphere is to act as a wife to her husband, a mother to her children, and a grandmother to her grandchildren. While in the public sphere Ende acts as a breadwinner and as a member of the community. Women traders by carrying out these two dual roles have implications for both the family and the community.